A novel classification for atypical Hangman fractures and its application: A retrospective observational study - Li, Guangzhou; Zhong, Dejun; Wang, Qing (Medicine (Baltimore), 2017)
Atypical Hangman fractures (AHF) were first formally reported and considered to be more often associated with neurologic deficit in 1993. However, there is a paucity of literature focusing on these fractures. The purpose of the retrospective study was to introduce a new classification scheme for AHF and its application.Sixty-two patients with Hangman fractures were identified. There were 46 (74.2%, 46/62) AHF patients, including 29 type I, 9 type II, 5 type IIa, and 3 type III fractures (Levine-Edwards classification). Based on fracture patterns, incidence, and their impact on neurologic status, a primary classification for AHF was devised. The clinical features of AHF were observed, and a new classification was introduced. The appropriate treatment strategy of AHF was discussed.Of 46 AHF patients, 27 underwent surgical treatment (24 with posterior approach with screw-rod fixation and fusion, 1 with anterior approach by C2/3 discectomy and fusion, and 2 with anterior and posterior approach), and the remaining 19 patients underwent nonoperative treatment. No patient complained severe neck pain at final follow-up. Neurologic status improved 1 to 2 grade in 12 cases with neurologic deficit. All patients achieved bony fusion within the follow-up period.AHF should be recognized as a distinct fracture subtype. The new classification for AHF is based on the feature of fracture patterns, injury mechanism, incidence, and their impact on neurologic deficit. And the new classification is complementary to Levine-Edwards.